Belajar Nilai Moral Melalui Drama Peraga: Penguatan Karakter Anak Melalui Teater Mini - Edo Dwi Cahyo; Asep Yudianto; Laili Ulfa (Prodi PGSD Unsultra, 2025)
This community service program aimed to strengthen moral character among elementary school students through drama-based learning. Conducted at MIN 3 Metro, the program involved 25 fifth-grade students and utilized participatory methods, including role-playing, scriptwriting, and drama performances. The activities were designed to enhance emotional intelligence, moral reasoning, and understanding of Pancasila values through experiential learning. Results showed significant improvements: a 72% increase in emotional recognition skills, an 80% reduction in bullying incidents, and 92% of student groups successfully integrating Pancasila principles into their scripts. Qualitative observations revealed profound personal transformations, such as increased confidence in shy students and improved conflict-resolution skills. The program also fostered unexpected outcomes, including the discovery of hidden talents and stronger peer collaboration. Key success factors included student-centered creative processes, simple technological integration for reflection, and strong collaboration with teachers. Challenges such as time constraints were overcome through innovative solutions like